Her, His, and their journey with endometriosis: a qualitative study - Shinan-Altman, Shiri; Wertheimer, Aya; Frankel, Bat-El; Hamama-Raz, Yaira (Frontiers in Global Women's Health, 2024)
BackgroundEndometriosis, impacting roughly 10% of reproductive-age women and girls globally, presents diagnostic challenges that can cause significant delays between symptom onset and medical confirmation. The aim of the current study was to explore the experience of women with endometriosis as well as that of their partners, from pre-diagnosis to diagnosis to post-diagnosis.MethodsIn-depth semi-structured interviews were conducted with 10 couples coping with endometriosis. Each partner was interviewed separately, and each interview was analyzed both individually and as part of a dyad, using the dyadic interview analysis method.ResultsThree main themes emerged: (i) “Relationship in the shadow of uncertainty”: Coping with health symptoms prior to the formal endometriosis diagnosis; (ii) Coping together or alone when receiving the endometriosis diagnosis; and (iii) “The day after the diagnosis”: Moving between adversity and growth.ConclusionsThe study's findings emphasize the importance of viewing the diagnosis from a dyadic perspective and comprehensively – that is, from pre-diagnosis to accepting the formal diagnosis to post-diagnosis. This journey can have a profound impact on both couple members, affecting their day-to-day functioning, communication, emotional and physical intimacy, and fertility.